(untitled) (Bangladesh Journal of Livestock Research, 2025)
This experiment determined the production and nutrient composition of Napier fodder cultivated at Barind area. Three Napier cultivars named BLRI Napier 3 (BN-3), BLRI Napier 4 (BN-4), and Napier Color Variety (NCV), were used to know its production and nutrient components at the experimental plots of Bangladesh Livestock Research Institute (BLRI) regional station (RS), Godagari, Rajshahi during the financial year 2022-23. The experiment was designed by three treatment groups (T1=BN-3, T2= BN-4 and T3= NCV) with five replications and the size of the experimental plots were (20 x 10) square feet. Composition of soil samples from each of the experimental plots were collected and examined from the Divisional Laboratory of Soil Resource Development Institute (SRDI), Rajshahi. First harvest was performed at 60 days after planting and following at 50 days intervals. Data from five successive harvests were gathered and statistically analyzed using SPSS software. The results showed no significant (p>0.05) differences in overall production parameters among the three cultivars. Biomass yield (ton DM/ha/cutting) in BN-4, BN-3 and NCV were found 9.18, 8.57 and 8.38, respectively. However, cultivars showed significant (p<0.05) variations in sheath weight, leaf weight, and leaf-to-stem ratio (LSR). The better LSR was estimated in BN-4 (0.47) compared to BN-3 (0.34) and NCV (0.38). Furthermore, Dry Matter (DM), Crude Protein (CP), Acid Detergent Fiber (ADF) and Ash in the whole plant were varied significantly (P<0.05) among three cultivars. In summary, the experiment indicates that BN-4 outperforms BN-3 and NCV in production yield, suggesting that BN-4 could be an ideal fodder cultivar for achieving optimal biomass yield in Barind areas. Bang. J. Livs. Res. Vol. 30 (1&2), 2023: P. 1-10